Simulation of Effect of Airfoil MH32 with Variation Taper Ratio and Angle of Attack Coefficient Lift and Drag Fixed wing Unmanned Aircraft - Satworo Adiwidodo; Andy Hermawan Wijaya (Asian Journal Science and Engineering, 2022)
Nowadays, the aerospace sector is growing very rapidly. One of the newest technologies is unmanned aerial vehicle. This UAV has functions to monitor disaster, mapping, espionage and shooting target. Therefore it needs a plane that can fly fast and agile. To achieve these characteristics, one of the most important things is the design of the wings. Some of the important parameters contained in the wings are the type of airfoil, aspect ratio, wing area, taper ratio, and angle of attack. The article aims to analyze the type of airfoil MH32 as well as the effect of the parameter taper ratio with variations of 0.2, 0.4, 0.6 in variations of angle of attack 0 °, 3 °, 6 °, 12 ° and 15 ° to the value of coefficient of lift and coefficient of drag. The method used in this research is experimental with a computational approach using a computer, the advantage of this method is that it does not need a real plane shape. The type of simulation used is Computational Fluid Dynamic (CFD) found in Ansys Fluent. From the simulation, value of coefficient of lift, coefficient of drag, and image of pressure contour and streamline velocity were obtained. All the data was processed and analyzed, then the result is that the taper ratio 0.4 has the highest lift to drag ratio of 19,417. It means that it has the highest value of the coefficient of lift and has the lowest coefficient of drag. These simulated results are validated with experimental from UIUC (University of Illinois at Urbana-Champaign) 1996. The conclusion of this study is that the smaller the taper ratio, the greater the value of the lift coefficient. Then increase the angle of attack to make the value of the lift coefficient is also getting bigger. Keywords: Simulation Effect Airfoil, Coefficient Lift, Coefficient Drag